PROFESSIONALIZATION FOR GRADUATE EMPLOYABILITY IN CAMEROON HIGHER EDUCATION: OLD WINE IN NEW WINESKINS? - Bilola, Theresia; Pascal, Doh (The Modern Higher Education Review, 2017)
One issue to which higher education (HE) is increasingly expected to respond is graduate employability. In addition to its traditional missions, Cameroon HE is expected to pursue priority objectives. At independence, Cameroon HE was to train indigenes to replace expatriates in the state administration. However, the saturation of the state machinery obliged reforms and modified objectives. In a study including interviewees from the ministry of higher education and one state university, ‘professionalization for employability’ was identified as one of such objectives. The respondents were chosen on the basis of relevance to the topic, availability and willingness to respond. We discuss the origins and rationale of professionalization at independence and after the 1993 reforms. A peculiarity of professionalization is its articulation as a new ‘objective’ in universities. Using the Newmanian and the Market-Model perspectives, we argue that the novelty is in the attention, type of stakeholders and approaches and not in professionalization itself. It was noticed that some academics do not agree that universities should be concerned with employability of graduates. This is due to the belief in education for its own sake without utilitarian motives as well as uncertainty about the capacity of the national labour market. Even though the efforts have addressed both the supply and demand side of the products of HE, the supply side is insufficiently addressed. We conclude that professionalization; in the way it is currently being addressed cannot enhance graduate employment and relevance of university education to the job market as intended.